Predictors of survival among children and adolescents with rhabdomyosarcoma treated in a single resource-limited centre —Uganda - Richard Nyeko; Fadhil Geriga; Racheal Angom; Joyce Balagadde Kambugu; Jaques van Heerden (BMC Cancer)
Abstract Background The treatment outcomes for children and adolescents with rhabdomyosarcoma (RMS) in low-income countries are poor. However, there is a paucity of literature on RMS and its management outcomes in low-resource settings. We evaluated the treatment of RMS with the aim of identifying prognostic factors during management to improve outcomes. Methods We sourced data on children under 18 years treated for rhabdomyosarcoma at the Uganda Cancer Institute between January 2016 and December 2020. Kaplan-Meier survival analysis and Cox’s proportional hazards model were used for five-year survival analysis. Results One hundred twenty-eight RMS cases were identified, with a median age of 6.0 years (IQR 3.6–10.0). The most common primary tumour site was the head and neck region, comprising non-parameingeal sites, 37 (28.9%); parameingeal sites, 32 (25.0%); and orbital tumours, 17 (13.3%). Overall, 68 (53.1%) of the primary tumour sites were unfavourable sites. Seventeen (13.3%) patients had metastatic disease at diagnosis, primarily to the lungs, 11 (64.8%). Embryonal and alveolar RMS accounted for 50.0% and 20.3% of the cases, respectively. Only 31 (24.2%) of the patients underwent surgery, and 36 (28.1%) were irradiated. The treatment completion rate was 33.6%, while 46.1% abandoned treatment. Only 25 (19.5%) patients were alive at the time of the study, 65 (50.8%) had died, and 38 (29.7%) had an unknown status. The five-year overall and event-free survival rates were 35% and 30%, respectively. Orbital primary tumour site (HR = 2.86; 95% CI 1.12–7.31; p = 0.028), metastatic disease (HR = 4.09; 95% CI 2.01–8.31; p < 0.001), elevated serum lactate dehydrogenase at diagnosis above 400 U/L (HR = 2.80; 95% CI 1.46–5.33; p = 0.002), and lack of local control (HR = 3.33; 95% CI 1.34–8.29; p = 0.010) were significant factors for poor survival. Conclusion Rhabdomyosarcoma outcomes in Ugandan children are largely poor, with high treatment abandonment and mortality. Concerted, multidisciplinary efforts are needed to improve outcomes in this setting.